Personality and Its Partisan Political Correlates Predict U.S. State Differences in Covid-19 Policies and Mask Wearing Percentages - Heyman, Gene M. (Frontiers in Psychology, 2021)
A central feature of the Covid-19 pandemic is state differences. Some state Governors closed all but essential businesses, others did not. In some states, most of the population wore face coverings when in public; in other states, less than 50% wore face coverings. According to journalists, these differences were symptomatic of a politically polarized America. The Big 5 personality factors also cluster at the state level. For example, residents of Utah score high on Conscientiousness and low on Neuroticism, whereas residents of Massachusetts and Connecticut show the opposite pattern. In state-level regressions that controlled for partisan political allegiances, Conscientiousness was a significant (negative) predictor of the stringency of state Covid-19 restrictions, whereas Openness was a significant (positive) predictor of mask wearing. A number of the predictors were strongly correlated with each other. For example, the correlation coefficient linking Openness with the percentage of Democratic state legislators was r = 0.53. Commonality regression partitions the explained variance between the amount that is unique to each predictor and the amount that is shared among subsets of correlated predictors. This approach revealed that the common variance shared by Conscientiousness, Openness and partisan politics accounted for 34% of the state differences in Covid-19 policy and 35% of the state differences in mask wearing. The results reflect the importance of personality in how Americans have responded to the Covid-19 pandemic.